Identifikasi Karbon Monoksida Dalam Darah Pada Penjual Buah Di Jembatan Kembar Sungguminasa - Rustiah, Waode; Fatmawati, Andi; Ashrafiyah, Ashrafiyah (Lontara Journal of Health Science and Technology, 2021)
The chemical compound of CO gas is a gas that has no color and contributes greatly to environmental pollution as a result of incomplete combustion of fuel produced from motor vehicles. Carbon monoxide is very dangerous (toxic, so it is often referred to as the "silent killer". The presence of CO gas will be very dangerous if inhaled by humans because the gas will replace the position of oxygen that binds to hemoglobin in the blood. The purpose of the study was to identify the presence or absence of carbon monoxide (CO) in the blood of fruit sellers at the Sungguminasa Twin Bridge. This research is an analytical observational field research using the alkaline dilution test method. The sampling technique used purposive sampling with the criteria of working more than one year, working 8 hours a day and not smoking. The number of samples used as many as 9 samples of venous blood. From the results of this study, it can be concluded that the presence of carbon monoxide gas was not identified in all blood samples of fruit sellers at the Sungguminasa Twin Bridge. This is because in the alkaline dilution test method, CO gas can only be identified with saturation levels above 20%.